Legal Certainty of the Roya Konsen Deed as an Administrative Instrument in the Crossing Out of Dependent Rights - Ari Rafsanjani; Gusti Yosi Andri; Zelfi Ghaffar Aufiyah (Journal Of Social Science (JoSS), 2026)
This study examines the legal certainty of the roya konsen deed as an administrative instrument in the process of crossing out dependent rights when the Certificate of Dependent Rights is lost. Land administration requires legal certainty to ensure orderly registration, protection of rights, and accuracy of juridical land data. In practice, the loss of the Certificate of Dependent Rights often creates obstacles in the roya process, encouraging the use of the roya konsen deed as a substitute administrative document. The purpose of this research is to analyze the legal position and legitimacy of the roya konsen deed in the implementation of roya and to assess its conformity with the principle of legal certainty in the land law system. This study employed an empirical legal research method with a sociological juridical approach. Data were obtained through literature studies, legal document analysis, and interviews with employees of the Cirebon City Land Office and notaries involved in drafting roya konsen deeds. The findings indicate that the roya konsen deed functions as an authentic deed with strong evidentiary value that supports administrative certainty in land registration practices. However, the deed does not possess executorial power equivalent to the Certificate of Dependent Rights and lacks explicit normative regulation within statutory law. The study concludes that the roya konsen deed has practical effectiveness in maintaining land administration order, but stronger normative legitimacy through Ministerial Regulation is necessary to ensure legal certainty, procedural uniformity, and administrative consistency in roya services.